"La delegacion de India durante su visita al techo de la casa CNT/FAI. D.i.a.d.: 1. Rodriguez Vazquez, 2. (?), 3. Gandhi 4. Nehru." Series of 2 photos. Copied from CNT collection
"La delegacion de India durante su visita al techo de la casa CNT/FAI. D.i.a.d.: 1. Rodriguez Vazquez, 2. (?), 3. Gandhi 4. Nehru." Series of 2 photos. Copied from CNT collection.